Calculating lactate anaerobic thresholds in sports involving different endurance preparation - Stanula, A.; Gabrys, T.; Szmatlan-Gabrys, U.; Roczniok, R.; Maszczyk, A.; Pietraszewski, P. (Journal of Exercise Science & Fitness, 2013)
The aim of this study was to establish the degree of similarity of exercise intensity values at the anaerobic threshold (AT) provided by five methods of lactate curve analysis, i.e., LTAT, LTloglog, 1 mmol AT, 4 mmol AT, and D-max. The pattern of similarities and differences was sought in athletes with varying levels of experience and sports skills, representing two disciplines with different prevailing types of power output during competition: on-road cycling (aerobic metabolism) and ice-hockey (anaerobic metabolism).